Spatial mode rotator based on mechanically induced twist and bending in few-mode fibers - Yu, Dawei (2018)
Recently, few-mode fiber (FMF) based mode division multiplexing (MDM) transmission together with multi-input multi-output (MIMO) signal processing technique is ideal candidate to solve future single mode fiber (SMF) capacity crunch. Most existing mode division multiplexers/demultiplexers (MMUX/DEMMUX) have a specific mode orientation for high-order non-circular symmetric mode. Taking the phase plate based DEMMUX as example and converting LP11 mode to fundamental LP01 mode, we need optimize input mode orientation the same as the phase pattern of phase plate. In this submission, we propose and experimentally demonstrate a spatial mode rotator based on mechanically induced twisting and bending in a step-index FMF. We theoretically find that the mode coupling strength between vector modes with similar propagation constants is determined by the FMF bending and twisting. When the input LP11 mode cluster including TE01, HE21a, HE21b, and TM01 mode are properly perturbed, the output optical field is superposed as LP11 mode with a rotation. Therefore, the proposed spatial mode rotator is composed of three FMF coils with a radius of 16 mm, while the number of each coil is 2, 1, and 2, respectively. Consequently, we are able to rotate the LP11 mode with arbitrary angle within 360° range using the same conventional configuration of polarization controller (PC). The insertion loss of proposed spatial mode rotator is less than 0.82 dB, when the operation wavelength varies from 1540 nm to 1560nm. In particular, from the measured mode profile, there exists little crosstalk between LP01 mode and LP11 mode during mode rotation operation.